Study the influences of the radionuclide depth distributions on the FEPE for the measurements of the soil activity using in situ HPGe gamma spectrometry - Truong Thi , Hong Loan; Vu, Ngoc Ba; Le Hung, Quoc Dan; Truong Huu, Ngan Thy; Huynh Thi , Yen Hong (Nuclear Science and Technology, 2017)
In this work, the influences of the soil densities and the radionuclide depth distributions (RDD) on the Full Energy Peak Efficiency (FEPE) calculation of the in-situ gamma ray spectrometer using the In Situ Object Counting Systems (ISOCS) software were studied. The data of the RDDs at the sites were investigated by using laboratory HPGe gamma spectrometer. Six different RDDs of 40K, 226Ra and 232Th were found at four studied sites with radionuclide deposition moving from surface to deeper positions. The results show that FEPE values vary strongly for the different RDDs, especially for the low gamma ray energies. Use of the uniform model for calculating FEPEs can result in noticeable errors from 29% to 101% for the realistic RDD of the exponential form (surface radionuclide deposition), negative variations from 14% to 30% for the realistic RDD of having a radionuclide deposition at the 30 cm depth, and negligible variations of less than 5 % for the realistic RDD of quasi uniform form in the range of gamma ray energies of interest.